EUROPEAN FEMALE CHARACTERS IN THE WORKS OF AHMET MİTHAT EFENDİ AND İSMAİL GASPIRALI (Third Sector Social Economic Review, 2019)
This paper aims to explore European women characters in selected works of  Ahmet Mithat Efendi (1844-1912) and İsmail Gaspıralı (1851-1914). This particular focus facilitates the reader to revise  some major claims and generalisations that were made on the post-Tanzimat literatüre. It also underlines the plurality of views and approaches existing during that period. In this paper, European female characters are focused and analysed in the novel of Ahmet Mithat Efendi Acâyib-i Âlem (1881-82) and; in the narratives of İsmail Gaspıralı “Frengistan Mektupları” (1887) and “Sudan Mektupları” (1889).The paper is concluded by pointed out that in these novel and narratives the European women guided the Ottoman men by using their knowledge. The European culture and especially the positive sciences were also introduced the to the “Eastern” men through the European women. In essence these novels the European women are portrayed as the dominant part in their relationship with the “Eastern men”. It is because of these women a reversal in the traditional hierarchy between genders occured.
Keywords: European Women; Muslim Men; Traditional Hierarchy